Italy on the spotlight: Expo Milan 2015 and Italian Journal of Food Science - P. Fantozzi; M.F. Caboni; T. Gallina Toschi; V. Gerbi; A. Hidalgo; V. Lavelli; G. Perretti; P. Pittia; C. Pompei; K. Rantsiou; L. Rolle; M. Sinigaglia; et al. (Chiriotti Editori, 2015)
The year 2015 will certainly be remembered as the Year of the Universal Exposition (EXPO) hosted in Milan, Italy, focusing on a hot theme in the current scenario: "Feeding the Planet, Energy for Life". This event has drawn a wide international attention towards Italy as a country with peculiar and valuable food traditions, thus strengthening its reputation as "gastronomic capital of the world" rich in protected designation of origin products (PDOs) and characterised by a longstanding food culture.